Suitability and setup of next-generation sequencing-based method for taxonomic characterization of aquatic microbial biofilm - Bakal, Tomas; Janata, Jiri; Sabova, Lenka; Grabic, Roman; Zlabek, Vladimir; Najmanova, Lucie (Folia microbiologica, 2019)
A robust and widely applicable method for sampling of aquatic microbial biofilm and further sample processing is presented. The method is based on next-generation sequencing of V4-V5 variable regions of 16S rRNA gene and further statistical analysis of sequencing data, which could be useful not only to investigate taxonomic composition of biofilm bacterial consortia but also to assess aquatic ecosystem health. Five artificial materials commonly used for biofilm growth (glass, stainless steel, aluminum, polypropylene, polyethylene) were tested to determine the one giving most robust and reproducible results. The effect of used sampler material on total microbial composition was not statistically significant; however, the non-plastic materials (glass, metal) gave more stable outputs without irregularities among sample parallels. The bias of the method is assessed with respect to the employment of a non-quantitative step (PCR amplification) to obtain quantitative results (relative abundance of identified taxa). This aspect is often overlooked in ecological and medical studies. We document that sequencing of a mixture of three merged primary PCR reactions for each sample and further evaluation of median values from three technical replicates for each sample enables to overcome this bias and gives robust and repeatable results well distinguishing among sampling localities and seasons.
Keywords: Sequence Analysis, DNA; mikrobiota; Environmental Monitoring; Water Microbiology; RNA ribozomální 16S; Microbiota; RNA, Ribosomal, 16S; reprodukovatelnost výsledků; sekvenční analýza DNA; monitorování životního prostředí; biofilmy; Reproducibility of Results; vysoce účinné nukleotidové sekvenování; High-Throughput Nucleotide Sequencing; Specimen Handling; mikrobiologie vody; Bacteria; odběr biologického vzorku; Biofilms